PENERAPAN MODEL PENGAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA - Kharani, Kharani (Jurnal Pendidikan Guru, 2018)
This study aims to improve science learning outcomes of fourth graders Elementary School 014 Buluh Kasap by applying direct teaching model. The subject of this research is the fourth grader of SD Negeri 014 Buluh Kasap which is 24 students. The large increase in student learning outcomes can be seen from the basic score of 66.45 up 12.87% to 75 in cycle I. Furthermore, in cycle II there is an increase in learning outcomes 21.32% of the basic score with the average UH results of cycle II of 80.62. While for teacher activity and student activity also increase, in cycle I meeting I the percentage of teacher activity is 58,33% with enough category, and increase at meeting II to 72,22% with good category. Furthermore, in the second cycle of meeting I the percentage of teacher activity increased to 83.33% with very good category as well as at the second meeting increased again to 91.66% with very good category. Similarly, student activity, on the first cycle of meeting I the percentage of student activity is 55.55% with sufficient category, and increased at the second meeting to 69.44% with good category. Next on the second cycle of meeting I the percentage of student activity increased to 80.55% with very good category as well as at the second meeting increased again to 91.66% with very good category. Conclusion that Implementation of Direct Teaching Model can increase Improve Results of Science Student grade IV SD Negeri 014 Buluh Kasap.